Preparation method of tough polyrotaxane hydrogel humidity brake and prepared tough polyrotaxane hydrogel humidity brake

The strong polyrotane hydrogel humidity brake was prepared by polymerizing acrylic acid, vinyl polyrotane and vinyl triethoxysiloxane under the conditions of photoinitiator and ultraviolet light, and the current situation was solved There are problems of insufficient material strength and toughness, which achieves high mechanical strength and toughness, and is suitable for humidity brakes in harsh driving scenarios.

CN119119375AInactive Publication Date: 2024-12-13HUBEI INST OF AEROSPACE CHEMOTECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411418292.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing humidity brake materials have low mechanical strength, poor toughness, small shrinkage and weak functional capabilities, making it difficult to meet the needs of harsh driving scenarios.

Method used

Polytropic polyrotorane is prepared by polymerization under photoinitiator and ultraviolet light irradiation, using acrylic acid as a monomer, vinyl polyrotorane as a crosslinking agent, and vinyl triethoxysiloxane as a reinforcement. Hydrogel humidity brakes that enhance material strength and toughness through polymerization and tensile relaxation processes.

Benefits of technology

The prepared strong polyrotane hydrogel humidity brake has high mechanical strength, toughness and shrinkability. It is suitable for applications under harsh conditions and can significantly improve the driving ability of objects under moisture drive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119375A_ABST
    Figure CN119119375A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a tough polyrotaxane hydrogel humidity brake and the prepared tough polyrotaxane hydrogel humidity brake. The preparation method of the tough polyrotaxane hydrogel humidity brake comprises the steps that under the conditions of a photoinitiator and ultraviolet irradiation, the tough polyrotaxane hydrogel humidity brake is prepared; acrylic acid as a monomer, vinyl polyrotaxane as a cross-linking agent and vinyl triethoxy siloxane as a reinforcing agent are subjected to a polymerization reaction to obtain the tough polyrotaxane hydrogel humidity brake, and the tough polyrotaxane hydrogel humidity brake shows a super-shrinkage behavior when meeting moisture, so that PHFB has the capability of being used as the humidity brake and can lift an object under the driving of moisture. The PHFB tough polyrotaxane hydrogel humidity brake is large in mechanical strength, high in toughness, high in contractibility and high in power capability, and can be used as a powerful fiber humidity brake.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of humidity brakes, and in particular to a method for preparing a strong and tough polyrotaxane hydrogel humidity brake and the prepared strong and tough polyrotaxane hydrogel humidity brake. Background Art

[0002] In recent years, the widespread application of humidity brakes has put forward higher requirements on the properties of materials, requiring them not only to have high driving performance, but also to have good strength and toughness to meet more stringent driving scenarios. Currently, the most widely used humidity brake fibers use materials such as silk, polyethylene-polypyran film, twisted carbon nanotube yarn, carbon nanotube / resin yarn, nylon 6 fishing line, nickel-titanium wire and twisted lotus fiber as driving materials, and these materials have more or less disadvantages such as low mechanical strength, poor toughness, low shrinkage and weak working capacity, which is not conducive to the preparation of fiber humidity brakes used in harsh driving scenarios.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a strong and tough polyrotaxane hydrogel humidity brake and the prepared strong and tough polyrotaxane hydrogel humidity brake, so as to provide a humidity brake with high mechanical strength and toughness.

[0005] The present invention is achieved in that:

[0006] In a first aspect, the present invention provides a method for preparing a tough polyrotaxane hydrogel humidity brake, comprising:

[0007] Under the conditions of photoinitiator and ultraviolet light irradiation, a polymerization reaction is carried out with acrylic acid as a monomer, vinyl polyrotaxane as a crosslinking agent and vinyl triethoxysiloxane as a reinforcing agent to obtain the tough polyrotaxane hydrogel humidity brake.

[0008] In an optional embodiment, the average molecular weight of the vinyl polyrotaxane is 2000 to 35000, and the cyclodextrin inclusion rate on the main chain of the vinyl polyrotaxane is 2% to 10%.

[0009] In an optional embodiment, the molar ratio of acrylic acid to vinyl polyrotaxane is 0.8×10 3 ~3.4×10 3 ;

[0010] And / or, the molar ratio of acrylic acid to photoinitiator is 0.6×10 3 ~1.7×10 3 ;

[0011] And / or, the photoinitiator is selected from photoinitiator 1173.

[0012] In an optional embodiment, it includes:

[0013] Step 1: preparing a reinforcing solution including vinyl triethoxysiloxane and water;

[0014] Step 2: adding acrylic acid, a photoinitiator and vinyl polyrotaxane to the reinforcing liquid to obtain a prepolymer liquid;

[0015] Step 3: inserting a capillary into the prepolymer solution, and under ultraviolet light irradiation, making the capillary at least partially filled with the prepolymer solution and performing the polymerization reaction to obtain a polymer;

[0016] Step 4: removing the capillaries in the polymer and stretching, relaxing and drying the polymer to obtain the strong polyrotaxane hydrogel humidity brake.

[0017] In an optional embodiment, the molar ratio of vinyl triethoxysiloxane to water in the reinforcing solution is 3.3×10 -3 ~3×10 -2 ;

[0018] And / or, the molar volume ratio of the acrylic acid to the reinforcing liquid is 0.33×10 3 mol / ml~0.56×10 3 mol / ml.

[0019] In an optional embodiment, the ultraviolet light irradiation time is 1.8h to 2.2h, and the ultraviolet light wavelength λ is 200-400nm;

[0020] And / or, the filling and polymerization reactions are both carried out under vacuum conditions;

[0021] And / or, the inner diameter of the capillary 50μm~100μm

[0022] In an optional embodiment, the polymer is stretched to a strain of 18% to 20% and then relaxed, and the stretching and relaxing are alternately performed 1 to 15 times;

[0023] And / or, the stretching and the relaxing are both performed under the condition of relative humidity of 70% to 99%.

[0024] And / or, the drying temperature is 18° C. to 25° C., the drying method is hanging weight drying, and the hanging weight during drying is 30 MPa to 50 MPa.

[0025] In a second aspect, the present invention provides a tough polyrotaxane hydrogel humidity brake prepared by the method described in any one of the aforementioned embodiments.

[0026] In an optional embodiment, it is a pleated sheath-core structure, the spacing between adjacent pleats is 150nm-2000nm, and the thickness of the sheath formed by the pleats is 5μm-20μm.

[0027] The present invention has the following beneficial effects:

[0028] In the preparation method of the tough polyrotaxane hydrogel humidity brake of the present application, a polymerization reaction is carried out using vinyl polyrotaxane (EPR) as a cross-linking agent, wherein the vinyl polyrotaxane includes a linear polymer chain and a macrocyclic molecule such as cyclodextrin, wherein the macrocyclic molecule can slide on the linear polymer chain, so that the polymer obtained using it as a cross-linking agent can disperse stress well, which is beneficial to the improvement of the strength and toughness of the polymer.

[0029] In addition, the introduction of vinyl triethoxysiloxane can increase the cross-linking points in the polymer, allowing the polymer to form a more complex, multi-layered three-dimensional network, which can further improve the strength and toughness of the polymer.

[0030] The PHFB (polyrotaxane hydrogel fiber) prepared in this application exhibits super-contractile behavior when wet, which enables PHFB to act as a moisture brake and lift objects under the drive of moisture. The strong polyrotaxane hydrogel moisture brake has high mechanical strength, strong toughness, high contraction and strong working ability, and has a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a schematic diagram of the humidity brake prepared in Example 1 generating actuation after the humidity is changed;

[0033] Figure 2 This is the SEM image of the humidity brake prepared in Example 1;

[0034] Figure 3 This is a comparison chart of the mechanical properties of the humidity brakes prepared in Example 2, Comparative Example 1 and Comparative Example 2;

[0035] Figure 4 This is the SEM image of the humidity brake prepared in Example 2;

[0036] Figure 5 The fiber shrinkage force of the humidity brake prepared in Example 7 changes with time at different humidity levels;

[0037] Figure 6 This is the cyclic training stability of the humidity brake prepared in Example 7 under a relative humidity of 95% and an isobaric load of 23 MPa. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] In a first aspect, the present invention provides a method for preparing a tough polyrotaxane hydrogel humidity brake, comprising:

[0040] Under the conditions of photoinitiator and ultraviolet light irradiation, a polymerization reaction is carried out with acrylic acid as a monomer, vinyl polyrotaxane as a crosslinking agent and vinyl triethoxysiloxane as a reinforcing agent to obtain the tough polyrotaxane hydrogel humidity brake.

[0041] In the preparation method of the tough polyrotaxane hydrogel humidity brake of the present application, a polymerization reaction is carried out using vinyl polyrotaxane as a cross-linking agent, wherein the vinyl polyrotaxane includes a linear polymer chain and a macrocyclic molecule such as cyclodextrin, wherein the macrocyclic molecule can slide on the linear polymer chain, so that the polymer obtained using it as a cross-linking agent can disperse stress well, which is beneficial to the improvement of the strength and toughness of the polymer.

[0042] In addition, the introduction of vinyl triethoxysiloxane can increase the cross-linking points in the polymer, allowing the polymer to form a more complex, multi-layered three-dimensional network, which can further improve the strength and toughness of the polymer.

[0043] The polymer obtained by the method of the present application not only has high strength and toughness, but also has a shrinkage rate of up to 92% when the humidity increases to 70-99%. It also has high working capacity and can be suitable for humidity brakes used under harsh conditions.

[0044] In an optional embodiment, the average molecular weight of the vinyl polyrotaxane is 2000 to 35000, and the cyclodextrin inclusion rate on the main chain of the vinyl polyrotaxane is 2% to 10%.

[0045] The average molecular weight and cyclodextrin inclusion rate will affect the sliding of cyclodextrin on the linear polymer chain, and further affect the strength and toughness of the prepared polymer. Within the above range, a humidity brake with good strength and toughness can be obtained.

[0046] In an optional embodiment, the molar ratio of acrylic acid to vinyl polyrotaxane is 0.8×10 3 ~3.4×10 3 ;

[0047] And / or, the molar ratio of acrylic acid to photoinitiator is 0.6×10 3 ~1.7×10 3 ;

[0048] And / or, the photoinitiator is selected from photoinitiator 1173.

[0049] When the amount of cross-linking agent is within the above range, it is more beneficial to improve the mechanical strength and stability of the polymer. Excessive cross-linking agent will cause the material to become too rigid or even brittle and fracture. When the amount of photoinitiator is within the above range, it is more beneficial to accelerate the polymerization reaction rate, improve the curing depth and mechanical properties. Excessive photoinitiator will cause problems such as decreased mechanical properties.

[0050] In an optional embodiment, it includes:

[0051] Step 1: preparing a reinforcing solution including vinyl triethoxysiloxane and water;

[0052] Step 2: adding acrylic acid, a photoinitiator and vinyl polyrotaxane to the reinforcing liquid to obtain a prepolymer liquid;

[0053] Step 3: inserting a capillary into the prepolymer solution, and under ultraviolet light irradiation, making the capillary at least partially filled with the prepolymer solution and performing the polymerization reaction to obtain a polymer;

[0054] Step 4: removing the capillaries in the polymer and stretching, relaxing and drying the polymer to obtain the strong polyrotaxane hydrogel humidity brake.

[0055] The introduction of capillaries during the polymerization process can act as a template, while also helping to reduce bubbles in the liquid and improve the orientation, strength and driveability of the polymer.

[0056] In an optional embodiment, the molar ratio of vinyl triethoxysiloxane to water in the reinforcing solution is 3.3×10 -3 ~3×10 -2 ;

[0057] And / or, the molar volume ratio of the acrylic acid to the reinforcing liquid is 0.33×10 3 mol / ml~0.56×10 3 mol / ml.

[0058] Vinyl triethoxysiloxane within the above range is more beneficial to improving the strength and toughness of the wet brake.

[0059] In an optional embodiment, the ultraviolet light irradiation time is 1.8h to 2.2h, and the ultraviolet light wavelength λ is 200-400nm;

[0060] And / or, the filling and polymerization reactions are both carried out under vacuum conditions;

[0061] And / or, the inner diameter of the capillary It is 50μm~100μm.

[0062] In an optional embodiment, the polymer is stretched to a strain of 18% to 20% and then relaxed, and the stretching and relaxing are alternately performed 1 to 15 times, preferably 8 to 10 times;

[0063] And / or, the stretching and relaxation are both performed under the condition of relative humidity of 70% to 99%. If the humidity is too low, cracks or even breaks are easily generated on the surface of the polymer during the stretching process.

[0064] Stretching and relaxing the polymer is beneficial to improving the orientation, strength and toughness of the polymer.

[0065] In an optional embodiment, the drying temperature is 18° C. to 25° C., the drying method is hanging weight drying, and the hanging weight during drying is 30 MPa to 50 MPa.

[0066] In a second aspect, the present invention provides a tough polyrotaxane hydrogel humidity brake prepared by the method described in any one of the aforementioned embodiments.

[0067] In an optional embodiment, it is a pleated sheath-core structure, the spacing between adjacent pleats is 150nm-2000nm, and the thickness of the sheath formed by the pleats is 5μm-20μm.

[0068] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0069] Embodiment 1:

[0070] This embodiment provides a method for preparing a tough polyrotaxane hydrogel humidity brake, comprising the following steps:

[0071] Step 1: Add vinyl triethoxysiloxane (20 mM) to deionized water (1.6 M) and stir vigorously for 12 hours until a transparent enhanced solution is obtained;

[0072] Step 2: Add acrylic acid (8.3 M), photoinitiator 1173 (8 mM) and vinyl polyrotaxane (3.5 mM, cyclodextrin inclusion rate X=5%, average molecular weight 32987 Da) to 18 mL of the above-mentioned enhancement solution to obtain a prepolymer solution;

[0073] Step 3: Insert the capillary Insert into the solution, fill by capillary effect, irradiate under 365nm UV lamp for 2 hours, and the whole process is carried out in a vacuum glove box;

[0074] Step 4: After the polymerization is completed and the polymer is obtained, the capillary is carefully broken from the middle, the polymer fiber is pulled, the stress is mounted at 50 MPa at 25°C, and dried for 6 hours to obtain the PHFB actuator.

[0075] like Figure 1 As shown in the figure, the strong polyrotaxane hydrogel humidity brake obtained in this example generates contraction drive when the humidity increases to 70-99%, and can carry a weight within 8000 times of its own weight. The PHFB strong polyrotaxane hydrogel humidity brake finally obtained in this example has been characterized by scanning electron microscopy test, as shown in the figure. Figure 2 As shown, the fiber surface is smooth and flat, with almost no lines and wrinkles.

[0076] Embodiment 2:

[0077] This embodiment provides a method for preparing a tough polyrotaxane hydrogel humidity brake, which is different from Embodiment 1 mainly in that the polymer is repeatedly stretched and relaxed, and specifically comprises the following steps:

[0078] Step 1: Add vinyl triethoxysiloxane (20 mM) to deionized water (1.6 M) and stir vigorously for 12 hours until a transparent enhanced solution is obtained;

[0079] Step 2: Acrylic acid (8.3 M), photoinitiator 1173 (8 mM) and EPR X (EPR x , 3.5 mM, cyclodextrin inclusion rate X = 5%, average molecular weight 32987 Da) was added to 18 mL of the above-mentioned enhancement solution to obtain a prepolymer solution;

[0080] Step 3: Insert the capillary Insert into the solution, fill by capillary effect, irradiate under 365nm UV lamp for 2 hours, and the whole process is carried out in a vacuum glove box;

[0081] Step 4: After the polymerization is completed and the polymer is obtained, the capillary is carefully broken from the middle, the polymer fiber is pulled, and the PHFB is obtained by drying at 25°C with a mounting stress of 50 MPa for 6 h.

[0082] Step 5: Under a relative humidity of 70%, stretch the PHFB to 20% strain and then relax it, repeatedly stretching it 15 times to obtain a strong polyrotaxane hydrogel humidity brake.

[0083] The tough polyrotaxane hydrogel humidity brake finally obtained in this example was tested as follows:

[0084] Mechanical properties tests, such as Figure 3 As shown in the figure, the tough polyrotaxane hydrogel humidity brake obtained in this example has a fracture strength of 0.88 GPa and a toughness of 310.8 MJ m -3 The strength and toughness of PHFB are significantly higher than those of PGHFB and FB. The trained PHFB was characterized by scanning electron microscopy. Figure 4 As shown, fine wrinkles appeared on the fiber surface, with the spacing between wrinkles being 150-2000nm. Scanning electron microscopy of the cross section showed that the fiber wrinkles formed a shell of 5-20μm.

[0085] Embodiment 3-6:

[0086] This embodiment provides a method for preparing a tough polyrotaxane hydrogel humidity brake, and studies the effect of the amount of vinyl polyrotaxane added on the brake performance, comprising the following steps:

[0087] Step 1: Add vinyl triethoxysiloxane (20 mM) to deionized water (1.6 M) and stir vigorously for 12 hours until a transparent enhanced solution is obtained;

[0088] Step 2: Add acrylic acid (8.3 M), photoinitiator 1173 (8 mM) and vinyl polyrotaxane (cyclodextrin inclusion rate X=5%, average molecular weight 32987 Da) to 18 mL of the above-mentioned enhancement solution to obtain a prepolymer solution, wherein the molar masses of the vinyl polyrotaxane in the prepolymer solution are 0.8 mM, 1.6 mM, 3.2 mM and 4.8 mM, respectively;

[0089] Step 3: Insert the capillary Insert into the solution, fill by capillary effect, irradiate under 365nm UV lamp for 2 hours, and the whole process is carried out in a vacuum glove box;

[0090] Step 4: After the polymerization is completed, the capillary is carefully broken from the middle, the polymer fiber is pulled, and dried at 25°C with a mounting stress of 50 MPa for 6 h.

[0091] Step 4: Under a relative humidity of 70%, PHFB was stretched to 20% strain and then relaxed, and the stretching was repeated 9 times to obtain a strong polyrotaxane hydrogel humidity brake.

[0092] The tough polyrotaxane hydrogel humidity brake finally obtained in this example was tested as follows:

[0093] The two ends of the PHFB were fixed on a mechanical tester to detect the driving stress generated and the maximum working capacity when lifting loads of different masses. In Example 4, the PHFB with a diameter of 45 μm had a corresponding loading stress of 50 MPa and a working capacity of 1.9 J kg at a relative humidity of 95%. -1 As shown in Table 1, when the loading stress is 50 MPa, the maximum working capacity of PHFB increases with the increase of the percentage of EPR added, but excessive addition of EPR will cause the strength and toughness of PHFB to decrease.

[0094] Embodiment 7:

[0095] This embodiment provides a method for preparing a tough polyrotaxane hydrogel humidity brake, and studies the effect of the vinyl polyrotaxane cyclodextrin inclusion rate X on the brake performance, comprising the following steps:

[0096] Step 1: Add vinyl triethoxysiloxane (20 mM) to deionized water (1.6 M) and stir vigorously for 12 hours until a transparent enhanced solution is obtained;

[0097] Step 2: Acrylic acid (8.3 M), photoinitiator 1173 (8 mM) and EPR X (EPR x , cyclodextrin inclusion rate X = 2.3%, average molecular weight 25123Da, added amount 3.5mM) was added to 18mL of the above-mentioned enhancement solution to obtain a prepolymer solution;

[0098] Step 3: Insert the capillary Insert into the solution, fill by capillary effect, irradiate under 365nm UV lamp for 2 hours, and the whole process is carried out in a vacuum glove box;

[0099] Step 4: After the polymerization is completed, the capillary is carefully broken from the middle, the polymer fiber is pulled, and dried at 25°C with a mounting stress of 50 MPa for 6 h;

[0100] Step 5: Under a relative humidity of 70%, stretch the PHFB to 20% strain and then relax it, repeatedly stretching it 9 times to obtain a strong polyrotaxane hydrogel humidity brake.

[0101] The tough polyrotaxane hydrogel humidity brake finally obtained in this example was tested as follows:

[0102] Fix the PHFB at both ends of the universal tensile machine fixture to test the law of the contraction force of the PHFB changing with the air humidity. Figure 5As the relative humidity of air increases from 20% to 100%, the shrinkage force of PHFB gradually increases. At the same humidity, the shrinkage force shows a three-stage change with time, that is, the shrinkage force first increases slowly, then rises sharply, and finally reaches a platform. After super shrinkage, PHFB is stretched to its initial length under high humidity and kept air-dried for the next cycle test of actuation. Figure 6 As shown, the PHFB prepared in Example 7 exhibits high driving stability in 300 driving cycles under a relative humidity of 95% and an isobaric load of 23 MPa.

[0103] Comparative Example 1:

[0104] The difference between this comparative example and Example 2 is that in step 1, 56 mM polyethylene glycol diacrylate (PEGDA) is used instead of EPR. X , the average molecular weight of polyethylene glycol diacrylate is 2000Da, and PGHFB is prepared.

[0105] Comparative Example 2:

[0106] The difference between this comparative example and Example 2 is that: in step 1, EPR is not added to prepare FB.

[0107] The performance of the humidity brake obtained in each embodiment and comparative example was tested. The mechanical property test method was to fix the two ends of the fiber on a universal tensile testing machine and stretch it at room temperature and an air humidity of 30% RH; the shrinkage work test conditions were the test conditions, the loading stress was 50 MPa, and the humidity was 95% RH. The test results are shown in Table 1.

[0108] Table 1 Mechanical properties and contraction work of the humidity brake obtained in each embodiment and comparative example

[0109]

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a tough polyrotaxane hydrogel humidity brake, characterized in that: include: Under the conditions of photoinitiator and ultraviolet light irradiation, a polymerization reaction is carried out with acrylic acid as a monomer, vinyl polyrotaxane as a crosslinking agent and vinyl triethoxysiloxane as a reinforcing agent to obtain the tough polyrotaxane hydrogel humidity brake.

2. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 1, characterized in that: The average molecular weight of the vinyl polyrotaxane is 2000-35000, and the cyclodextrin inclusion rate on the main chain of the vinyl polyrotaxane is 2%-10%.

3. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 1, characterized in that: The molar ratio of acrylic acid to vinyl polyrotaxane is 0.8×10 3 ~3.4×10 3 ; And / or, the molar ratio of acrylic acid to photoinitiator is 0.6×10 3 ~1.7×10 3 ; And / or, the photoinitiator is selected from photoinitiator 1173.

4. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 1, characterized in that: include: Step 1: preparing a reinforcing solution including vinyl triethoxysiloxane and water; Step 2: adding acrylic acid, a photoinitiator and vinyl polyrotaxane to the reinforcing liquid to obtain a prepolymer liquid; Step 3: inserting a capillary into the prepolymer solution, and under ultraviolet light irradiation, making the capillary at least partially filled with the prepolymer solution and performing the polymerization reaction to obtain a polymer; Step 4: removing the capillaries in the polymer and stretching, relaxing and drying the polymer to obtain the strong polyrotaxane hydrogel humidity brake.

5. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 4, characterized in that: The molar ratio of vinyl triethoxysiloxane to water in the reinforcing liquid is 3.3×10 -3 ~3×10 -2 ; And / or, the molar volume ratio of the acrylic acid to the reinforcing liquid is 0.33×10 3 mol / ml~0.56×10 3 mol / ml.

6. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 4, characterized in that: The ultraviolet light irradiation time is 1.8h to 2.2h, and the ultraviolet light wavelength λ is 200nm to 400nm; And / or, the filling and polymerization reactions are both carried out under vacuum conditions; And / or, the inner diameter φ of the capillary is 50 μm to 100 μm.

7. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 4, characterized in that: The polymer is stretched to a strain of 18% to 20% and then relaxed, wherein the stretching and relaxing are performed alternately 1 to 15 times; And / or, the stretching and the relaxing are both performed under the condition of relative humidity of 70% to 99%.

8. The method for preparing a tough polyrotaxane hydrogel humidity brake according to claim 4, characterized in that: The drying temperature is 18° C. to 25° C., the drying method is hanging weight drying, and the hanging weight during drying is 30 MPa to 50 MPa.

9. A tough polyrotaxane hydrogel humidity brake prepared by the method according to any one of claims 1 to 8.

10. The tough polyrotaxane hydrogel humidity brake according to claim 9, characterized in that: It is a folded sheath-core structure, the spacing between adjacent folds is 150nm-2000nm, and the thickness of the sheath formed by the folds is 5μm-20μm.

Citation Information

Patent Citations

  • Polyrotaxane quasi-slip ring hydrogel as well as preparation method and application thereof

    CN115124662A

  • Stereolithographic method and composition

    US20170333167A1

  • Photocurable composition, cured product formed from photocurable composition, and method for manufacturing said cured product

    US20170335044A1